Numerical simulation study on the effect of different oxygen-enrichment atmospheres on diesel combustion. (1st March 2023) - Wang, Wenchao; Li, Fashe; Wang, Hua
Abstract: Oxygen-rich combustion technology can improve fuel combustion efficiency and reduce pollutant emissions. It is one of the effective technical means to solve energy shortages and environmental pollution problems caused by rapid development of industry. In this paper, the combustion thermodynamic characteristics and pollutant emission of diesel fuel in different oxygen-rich atmospheres (oxygen-enriched air and fuel oxygen-rich atmosphere, and ethanol and biodiesel were selected in fuel oxygen-rich atmosphere) were investigated by numerical simulation. The results show that both oxygen-rich atmospheres increase the combustion temperature, flame temperature gradient, combustion heat release rate and flame propagation speed. The effect of oxygen-rich atmosphere on combustion is more severe, and the promotion effect of low oxygen-rich air on combustion process is more obvious. The flame thickness decreased in the two oxygen-rich atmospheres, and the flame thickness decreased significantly in the oxygen-enriched air atmosphere. Ethanol could reduce the flame thickness of diesel combustion more than biodiesel. The flame thickness was reduced from 0.03890 cm to 0.03214 cm with the addition of 20% ethanol. Oxygen-rich atmosphere can significantly inhibit the formation of soot precursor polycyclic aromatic hydrocarbons (PAHs) during diesel combustion, thereby reducing the amount of soot. However, the two oxygen-rich atmospheres have different effects on the formation of PAHs. The oxygen-rich atmosphere in the air mainly enhanced the oxidation reaction of PAHS with OH, O, H and other free radicals, resulting in a significant reduction in the production of PAHS . The fuel oxygen-rich atmosphere reduced the content of C2 –C4 and other small molecules substances, hindered the formation process of PAHS, and strengthened the oxidation reaction of PAHS . The smoke reduction effect of ethanol is better than that of biodiesel. By analyzing the reaction rate of PAHs formation path, it is determined that the main path of A1 affecting PAHs is R45 and R58. Highlights: A diesel-ethanol-biodiesel mechanism is proposed for combustion. Oxygen enrichment affects combustion thermal properties and PAHs production. Air oxygen-rich atmosphere significantly increases temperature and flame speed. Biodiesel and ethanol reduce the amount of C2 –C4 and raises the oxidation of PAHs. R45 and R58 are critical paths that affect the generation of A1.